FAKTOR – FAKTOR YANG MEMPENGARUHI PERILAKU SEKSUAL PADA REMAJA - Ghina Septiany Nurul Wahdah; Lia Nurcahyani (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2022)
Adolescence is one of the two periods of an individual's life span, where there are enormous physical changes, namely organ maturation and reproductive function. The problem that often occurs is the occurrence of risky sexual behavior. This study aims to determine the factors that influence sexual behavior in adolescents. The research design was cross sectional. The research population was 193 tenth grade students in Madrasah Aliyah Negeri 2 in the city of Cirebon. The research sample was 80 people who were taken by random sampling technique. The research instrument used a questionnaire, data analysis included univariate and bivariate with chi square. Results: Adolescents with high-risk sexual behavior were 13 people (16.3%), 16 people had low reproductive health knowledge (20%), and the role of parents was not good as many as 37 people (46.3%), and peer influence as high as 24 people (30%). There is a relationship between knowledge about reproductive health (p value 0.003), the role of parents (p value 0.006) and peer influence (p value 0.002) with adolescent sexual behavior.